Career Options for Scientists - Sever, Richard (Cold Spring Harb Perspect Biol, 2017)
Most PhD students in the biological sciences will not go on to become academics. For these individuals, choosing the best career path can be difficult. Fortunately, there are many options that allow them to take advantage of skills they hone during graduate and postdoctoral work.